A escrita da angústia em Graciliano: uma leitura psicanalítica - Rocha, Darislânia da Silva (2012)
The purpose of this MA thesis is to identify the role of the writing process in the novels São Bernardo (1934) and Angústia (1936), by Graciliano Ramos. In such novels, the first-person narrator/character experiences pain, grief and anguish, and expresses these feelings in the written word and in the very act of writing a book. We work on the hypothesis that the narrative act of the protagonists Paulo Honório and Luís da Silva points to the strength of the written word and to the possibility of creating from anguish and from grief. We focus on psychoanalysis as theoretical perspective, aiming to show that the act of expressing experience and the act of narrating – enabled by the act of writing – help the subject bear great losses and difficulties, in sublimation, which is an alternative that offers life and libidinal pleasure, instead of death and annihilation of the subject.